(untitled) - Tehmina Ambreen; Basrina Bibi; Abida Sultana; Ahmad Ullah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Linguistics deals with the characteristics and varieties of language, called the study of stylistics. Stylistics helps in understanding postmodern and modern literature beyond structure: regular patterns of phonology, morphology, syntax, and semantics. The article deals with the analysis of stylistic devices, also known as rhetorical devices and figures of speech. A stylistic device is a unique characteristic of a text that makes it different. These devices are tools for writers to make their writing compelling and influential. Every writer has a writing style that distinguishes them from other writers of their era, and over time, this writing style becomes their identity. These writings give hope and inspiration to the readers. The analysis here shows that Frost portrayed realistically New England life, using language and circumstances intimate to the public. His poetry is interesting from a stylistic perspective. He used many stylistic devices to give a supplemental meaning, idea, or feeling. This article analyzes stylistic devices in the poem STOPPING BY WOODS ON A SNOWY EVENING. This analysis will offer a new outlook on the poem to make it more fascinating for the reader.